Association of tumor necrosis factor alpha-308 promoter polymorphism with spondyloarthritides patients in Colombia (2012)
The pathogenesis of SpA is considered to be a complex and multi-factorial process and, similar to other autoimmune diseases, includes the activity of proinflammatory cytokines such as TNF alpha. Our study compared the -308 promoter polymorphism of TNF alpha with TNF alpha levels, HLA-B27 status, age at the onset of symptoms, SpA subtype and the clinical degree of activity in Colombian SpA patients and healthy subjects (HS). Comparisons of the TNF alpha-308A genotype among HS and SpA patients (P = 0.004), uSpA patients (P = 0.040), ReA patients (P = 0.001), were significantly different and AS patients (P = 0.110), as were alleles for SpAs (P = 0.007) between patients with SpAs and controls. Initial exploratory analyses demonstrated that the TNF alpha-308 SNP genotype frequencies were different among SpA patients and HS in the Colombian population studied. Furthermore, there was no significant correlation with activity and functional clinical index, serum TNF alpha level or HLA B27 status. Allele frequencies, on the other hand, were correlated with the activity clinical index.